(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: Sexual dysfunction is common in women and causes serious problems in their lives through affecting their physical and mental health, self-esteem and quality of life. The aim of this study was to determine the frequency of sexual dysfunction in women referred to health centers in north east of Iran in 2016. Methods: The study was cross-sectional. The statistical population consisted of all married women referring to Shahroud health centers in 2016. A total of 478 married women were selected through multi-stage sampling and data extraction methods. Interviews and the (FSFI) questionnaire were used for data collection. Demographic information was also collected. Statistical analysis was performed by Chi-square and independent t-test. Results: The frequency of sexual dysfunction was 48.5% (232/478), which was obtained for each domain as follows: sexual pain disorder 49.8% (238/478), orgasm disorder 51.0% (244/478), lubrication disorder 51.0% ( 244/478), sexual desire disorder 23.2% (111/478), and stimulation disorder 11.3% (54/478), respectively. In this study, sexual dysfunction was significantly associated with age (P≤/0/003) and education (P≤/0/001), but and there was no significant relationship with contraceptive methods or number of children (P≤/0/32). Conclusions: According to research findings, the frequency of sexual dysfunction is relatively high in the community. It is suggested that counseling centers and sex education centers be established in health centers. Keywords: Dysfunction, Female, Northeast, Relate, Sexual.